2020
DOI: 10.1021/acs.langmuir.0c01799
|View full text |Cite
|
Sign up to set email alerts
|

Orienting Cellulose Nanocrystal Functionalities Tunes the Wettability of Water-Cast Films

Abstract: Cellulose nanocrystal (CNC)-based materials display apparently erratic wetting behaviors with contact angle (CA) variations as large as 30°from sample to sample. This work hypothesizes that it is the orientation of CNC amphiphilic functionalities at the interface with air that causes the variability in CA. By exploiting relationships with the Hansen solubility parameter theory, a set of surface tension parameters is proposed for both the polar and the non-polar surfaces of cellulose I β nanocrystals. These coe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
21
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 47 publications
(146 reference statements)
4
21
0
Order By: Relevance
“…The results showed that the CNCs’ film had strong hydrophilicity. Bruel et al [ 62 ] reported similar results. The static WCA of the film prepared from compressed CNC particles was 45°.…”
Section: Resultssupporting
confidence: 53%
“…The results showed that the CNCs’ film had strong hydrophilicity. Bruel et al [ 62 ] reported similar results. The static WCA of the film prepared from compressed CNC particles was 45°.…”
Section: Resultssupporting
confidence: 53%
“…This has been shown previously in the literature not only for surfaces focusing on superhydrophocity 42 but also surfaces with contact angles of <90°. 43 It is also found that contact angle on SPNC surfaces is shown to be more sensitive to surface tension in the hydrophobic (90° < θ < 150°) region than in the superhydrophobic region (150° < θ < 180°). Furthermore, the surface tension determination on contact angle is consistent with varying aqueous solutions (EtOH and PEG).…”
Section: Resultsmentioning
confidence: 95%
“…A recent work investigates this topic and nicely quantify several interfacial and interaction energies for CNCs reorientation at both solid and liquid interfaces. [30] Yet, the work only speculates details of interfacial alignment of CNCs and several convincingly conformations exist and support the broad values of experimental results.…”
Section: Cncbased Pickering Emulsionsmentioning
confidence: 73%
“…Adapted with permission. [30] Copyright 2020, American Chemical Society. charged groups on the NC surface, and/or of coordinating multivalent cations in solution.…”
Section: The Complex Role Of Hydroxyls: the Love-hate Relationship Between Nanocellulose And Watermentioning
confidence: 99%
See 1 more Smart Citation